THE USAGE OF FUNGI Trichoderma harzianum AND Aspergillus niger ON FERMENTATION OF BANANAS CORM (Musa sp.) - Hadist, Ibrahim (Universitas Djuanda Bogor, 2018)
The purpose of this study was to study the interaction between dosages of fungi (T. harzianum & A. niger) and fermentation duration on protein content, crude fiber of bananas corm, and to determine the best treatment in fermentation. The method used is a Completely Randomized Design (CRD) with factorial pattern. The first factor (D) is the dose of fungi (T. harzianum and A. niger): 0.1%; 0.2% and 0.3% and the second factor (L) the fermentation duration: 24 hours, 48 hours, 72 hours and 96 hours. All treatments were replicated two times. The variables that measured are: protein content and crude fiber content of the material. The data obtained were tested by F test, then Duncan analysis was carried out. The results of the experiment showed the interaction effect between the both factors on the protein content and the crude fiber of banana weevils. The treatment T. harzianum at a dose of 0.3% and 72 hours of fermentation gave the highest protein content and the lowest crude fiber in bananas corm.Key Word : banana weevil, fermentation, crude fiber, protein